INCREASING ENGLISH SPEAKING SKILLS USING YOUTUBE - Euis Meinawati; Danang Dwi Harmoko; Nazzala Aulia Rahmah; Nurmala - Dewi (Polyglot, 2020)
The purpose of this study was to find out if the ability to speak English effectively by 10th graders at SMA IT Rahmaniya was improved by using YouTube. This paper focused on implementing YouTube as a method for teaching speaking that is different, interesting, and fun, while creating a classroom atmosphere that is comfortable and increases students’ enthusiasm for learning. This paper used the qualitative descriptive method as the method of research. The result of using YouTube was very effective because it allowed students to speak with more confidence and expression. They also did not have to worry about the phrases they used when speaking because they were able to see how foreigners speak English properly and correctly.BAHASA INDONESIA ABSTRAK: Tujuan dari penelitian ini adalah untuk mengetahui peningkatan ketermapilan berbicara bahasa inggris secara efektif dengan memanfaatkan media YouTube di SMA IT Rahmaniyah, untuk kelas X. Penelitian berfokus pada implementasi Youtube untuk pengajaran berbicara yang berbeda, menarik, menyenangkan, menjadikan suasana dikelas nyaman dan meningkatkan semangat belajar untuk siswa kelas X SMA. Penelitian ini menggunakan metode kualitatif deskriptif. Hasil dari penggunaan media YouTube selama pembelajaran di kelas sangat efektif, karena siswa berbicara dengan percaya diri dan lebih berekspresif. Siswa juga tidak perlu khawatir mengenai frasa yang mereka gunakan ketika berbicara bahasa inggris, karena mereka sudah melihat bagaimana orang asing berbicara bahasa inggris dengan baik dan benar.